Vitality and Application of Effect Size for Quality Research - Dhakal, Chuda (Journal of the Institute of Agriculture and Animal Science, 2023)
This review article highlights the importance of effect size in research. P-value alone is not sufficient to determine the practical significance of a study, making effect size an essential component in hypothesis testing. Choosing the appropriate effect size for a specific study design can be challenging, and its interpretation may require modifications and personal judgement. Therefore, researchers should exercise caution when reporting and interpreting effect size, as it provides valuable information about the practical significance of their study, complementing hypothesis testing results. In conclusion, effect size should not be overlooked and should be carefully chosen and interpreted to ensure the validity and reliability of research results